Encyclopedia of Mobile Phone Behavior 2015
DOI: 10.4018/978-1-4666-8239-9.ch080
|View full text |Cite
|
Sign up to set email alerts
|

Students Hurting Students: Cyberbullying as a Mobile Phone Behavior

Abstract: While technology can be educationally motivating for students of all ages, technology can also be a cruel tool in the hands of youngsters and teens who do not yet understand the implications and ramifications of remote and potentially anonymous communication. Texting and talking on a mobile cell phone encourages more uninhibited discourse than would likely occur in face-to-face conversation because the texter or talker sees no visual cues that signal the response of the recipient of the communication. Technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The projects are of varying sizes and also involve commercial firms who are heavily depend on OSS systems . During 2014, Google's mobile Android operating system had about one billion users across all devices (Conn 2014). A survey conducted in 2015 reported that almost 78% of companies run operations on open source software and 66% of companies have incorporated open source software in creating software for customers (BlackDuck 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The projects are of varying sizes and also involve commercial firms who are heavily depend on OSS systems . During 2014, Google's mobile Android operating system had about one billion users across all devices (Conn 2014). A survey conducted in 2015 reported that almost 78% of companies run operations on open source software and 66% of companies have incorporated open source software in creating software for customers (BlackDuck 2015).…”
Section: Introductionmentioning
confidence: 99%